Improvement of electrical capabilities of automotive lead-acid batteries in comparison with the one shot and two shot methodologies” - Pincay Pilay Dimas Alberto; Llosas Albuerne Yolanda Eugenia (Case Studies in Chemical and Environmental Engineering, 2022)
The use of the one shot methodology in production processes in terms of reduced operational costs and savings in consumption of inputs such as demineralized water and concentrated sulfuric acid can increase the electrical capacities of batteries and their durability, and it also increases their efficiency according to their life cycles (lifespan). This research was aimed at improving the formation or charging process of lead-acid batteries for automotive use through this methodology. This is a study based on a quantitative-experimental approach, with causal relationship between independent and dependent variables, used for description, analysis and explanation of phenomena, and it is manifested through stages of measurement, observation and verification of results, in order to obtain a real picture of the performance of automotive lead-acid batteries through one shot methodologies, thus enhancing their durability in the market or when used in the automotive industry.